(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To assess the prevalence of the cognitive impairment and the relation of some caridovascular risk factors in elderly patients admitted to Internal Medicine Department. Subject and method: A descriptive cross-sectional study in elderly patients (aged ≥60) admitted to Internal Medicine Department from 6/2023 to 8/2023. Results: The prevalence of the cognitive impairment in elderly patients admitted to Internal Medicine Department according to MMSE was 50%, with 26,6% being mild impairment, 19,15% moderate and 4,26% severe. Conclusion: Aging, coronary artery disease, post-stroke sequelae and lack of physical execise were factors related to the cognitive impairment in elderly patients.